(3GdGbJUGO GdQjGVj (B/s - (3GdLhGQj, efGVds ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2010)
(3eONd ddGbJUGO GdQjGVj h GdGbJUGO GdbjGSj , GdeUahaGJ h GSJNOGegG aj Md feGPL GdJhGRfGJ GdGbJUGOjI , GdVQGFH h CKQgG aj GdJhGRf GdGbJUGOj , LOhd GdeSJNOe `` GdefJL Ch LOhd djhfjJja , WQb Md GdeYGOdI GdNWjI , GdeQhfGJ h GdCeKdjI , OhGd GdGfJGL h GdJLGfS , GdJMdjd GdOjfGejcj h GdHQeLI GdNWjI eY hLhO CSFdI h JeGQjf YfO fgGjI cd aUd (B.s
(3eQGLY U(B.271 (3; LOGhd U(B.11 (3; GTcGd HjGfjI U(B.9s
Keywords: (3GdGbJUGOs; (3GdGbJUGO GdQjGVjs